2012
DOI: 10.3390/ijms13055789
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Base-Catalyzed Hydrolysis Rates or Glutathione Reactivity for Acrylates and Methacrylates and Their NMR Spectra or Heat of Formation

Abstract: The NMR chemical shift, i.e., the π-electron density of the double bond, of acrylates and methacrylates is related to the reactivity of their monomers. We investigated quantitative structure-property relationships (QSPRs) between the base-catalyzed hydrolysis rate constants (k1) or the rate constant with glutathione (GSH) (log kGSH) for acrylates and methacrylates and the 13C NMR chemical shifts of their α,β-unsaturated carbonyl groups (δCα and δCβ) or heat of formation (Hf) calculated by the semi-empirical MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…That is why the branched PVA aqueous solutions have bigger shear viscosity than that of the linear one at the same molecular weight at 20°C. According to the changes in the shear viscosity, it proves that the AMA units are not hydrolyzed, which is consistent with the fact that acrylic ester is not easy for hydrolysis . Therefore, the long branches can be saved.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…That is why the branched PVA aqueous solutions have bigger shear viscosity than that of the linear one at the same molecular weight at 20°C. According to the changes in the shear viscosity, it proves that the AMA units are not hydrolyzed, which is consistent with the fact that acrylic ester is not easy for hydrolysis . Therefore, the long branches can be saved.…”
Section: Resultssupporting
confidence: 70%
“…As reported, hyperbranched polymer usually has lower crystallinity even totally amorphous although the linear polymer is crystalline polymer, and with the increase of branched points, the polymer has good solubility in solvent compared to the corresponding linear polymer. In our experiments, very small amount of bifunctional monomer was introduced, it is predictable that the branch chain points are relatively low and the branch chain is relatively long, the movement of chain is less affected, so the crystallinity did not decrease too much …”
Section: Resultsmentioning
confidence: 84%
“…In general, the ester linkages of both MA and MMA were possibly hydrolyzed. However, MA should be more hydrolyzed than MMA because of the higher base‐catalyzed hydrolysis rate constant of MA than that of MMA 46 . Moreover, because MA is more hydrophilic than MMA, PMA rich regions might locate at microcapsule surface during suspension polymerization that are easily hydrolyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Methacrylate and acrylate monomers are esters with a reactive pi bond between the α and β carbons. Fujisawa and Kadoma [10] showed that varying α substitution (methacrylates are methyl α substituted while acrylates are not) and varying β substitution can have effects on the monomer resistance to hydrolysis. Although methacrylates and acrylates can be polymerized using ultraviolet (UV) light and a photoinitiator, previous work by Khademhosseini et al [11] has shown that crosslinking methods alternative to UV curing are readily available.…”
Section: Introductionmentioning
confidence: 99%